2004
DOI: 10.1158/0008-5472.can-03-3740
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Protein Kinase G Is Sufficient to Induce Apoptosis and Inhibit Cell Migration in Colon Cancer Cells

Abstract: The activation of protein kinase G (PKG) by cGMP has become of considerable interest as a novel molecular mechanism for the induction of apoptosis in cancer cells, because sulindac sulfone (exisulind, Aptosyn) and certain derivatives that inhibit cGMP-phosphodiesterases and thereby increase cellular levels of cGMP appear to induce apoptosis via this mechanism. However, other effects of these compounds have not been excluded, and the precise mechanism by which PKG activation induces apoptosis has not been eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
124
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 48 publications
5
124
0
Order By: Relevance
“…Further, exisulind was fully efficacious in suppressing tumor growth in the presence of a specific inhibitor of PKG I (24,25), eliminating the involvement of that kinase in mediating the antineoplastic effects of exisulind. Additionally, overexpression of PKG Ih did not significantly alter the antineoplastic potency of exisulind in colon cancer cells (36). Thus, the present observations support a model in which the antitumor effects of exisulind in colon cancer reflect the sequential recruitment and activation of multiple signaling components, other than exisulind-induced PKG Ih, which seems to be an epiphenomenon, rather than mechanistically related to exisulind-induced tumor suppression.…”
Section: Discussionsupporting
confidence: 61%
“…Further, exisulind was fully efficacious in suppressing tumor growth in the presence of a specific inhibitor of PKG I (24,25), eliminating the involvement of that kinase in mediating the antineoplastic effects of exisulind. Additionally, overexpression of PKG Ih did not significantly alter the antineoplastic potency of exisulind in colon cancer cells (36). Thus, the present observations support a model in which the antitumor effects of exisulind in colon cancer reflect the sequential recruitment and activation of multiple signaling components, other than exisulind-induced PKG Ih, which seems to be an epiphenomenon, rather than mechanistically related to exisulind-induced tumor suppression.…”
Section: Discussionsupporting
confidence: 61%
“…PKG levels/activity have been shown to be modulated in many disease conditions. For example, PKG expression is downregulated in diabetes or cancer (7,16,21). Our previous studies demonstrated that the NO and cGMP levels were decreased in kidney mesangial cells under highglucose conditions, resulting in decreased PKG kinase activity (45,48).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] The impairment of cyclic adenosine monophosphate (cAMP) or cyclic guanosine monophosphate (cGMP) generation by regulation of phosphodiesterases (PDEs) has been implicated in various cancer pathologies. 8,9 PDEs are enzymes that regulate cellular levels of cAMP/cGMP by controlling their degradation.…”
Section: Introductionmentioning
confidence: 99%